2016
DOI: 10.3389/fphys.2016.00107
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Enhances ADPKD Cell Apoptosis via the Intrinsic Pathway

Abstract: Progression of autosomal dominant polycystic kidney disease (ADPKD) is highly influenced by factors circulating in blood. We have shown that the hormone ouabain enhances several characteristics of the ADPKD cystic phenotype, including the rate of cell proliferation, fluid secretion and the capacity of the cells to form cysts. In this work, we found that physiological levels of ouabain (3 nM) also promote programmed cell death of renal epithelial cells obtained from kidney cysts of patients with ADPKD (ADPKD ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 82 publications
(105 reference statements)
1
11
0
Order By: Relevance
“…DNA damage has been recognized as one of the factors for cell death . However, herein, we just examined the integrity of DNA by TUNEL assay in ouabain‐treated cells and results showed that ouabain induced DNA damage in DU 145 cells (Figure B).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…DNA damage has been recognized as one of the factors for cell death . However, herein, we just examined the integrity of DNA by TUNEL assay in ouabain‐treated cells and results showed that ouabain induced DNA damage in DU 145 cells (Figure B).…”
Section: Discussionmentioning
confidence: 94%
“…46,47 DNA damage has been recognized as one of the factors for cell death. 48 However, herein, we just examined the integrity of DNA by TUNEL assay in ouabain-treated cells and results showed that ouabain induced DNA damage in DU 145 cells ( Figure 3B). Furthermore, ouabain increased the expression of DNA damage and repair-associated proteins including p-ATM Ser1981 , p-H2A.X Ser139 , and p-p53 Ser15 at 48 hours treatment but decreased that of p-MDM2 Ser166 , MDM2, p53, BRCA1, DNA-PK, MGMT at 48 hours treatment ( Figure 6A).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, upon ouabain binding the Na,K-ATPase interacts with neighboring molecular environment to downstream a number of signaling intracellular pathways (Xie and Askari, 2002 ; Aperia, 2007 ; Li and Xie, 2009 ; Fontana et al, 2013 ; Reinhard et al, 2013 ). In different cell types, ouabain has dual effects to promote programmed cell death (Xiao et al, 2002 ; Kulikov et al, 2007 ; Blanco and Venugopal, 2016 ) and to protect against apoptosis (Isaev et al, 2000 ; Dvela et al, 2012 ). Nanomolar ouabain concentrations were also shown to stimulate viability and proliferation of NT2 cells, precursors for human neuronal cells, by a mechanism involving Erk1/2 activation (Dvela et al, 2012 ).…”
Section: Cardiotonic Steroids and Cell Survivalmentioning
confidence: 99%
“…It remains uncertain whether it affects numerous cellular functions by inhibiting enzymatic activity that leads to modulation of ion homeostasis or by conformational changes of the α subunit and initiation of a signal transduction. The role of the Na,K-ATPase CTS binding site suggests its involvement in regulation of diverse cellular functions, including synaptic and neural processes (Lichtstein and Rosen, 2001 ; Goldstein et al, 2006 , 2011 ; Song et al, 2013 ), cell survival and neuroprotection (Golden and Martin, 2006 ; Dvela et al, 2012 ; Sibarov et al, 2012 ; Dvela-Levitt et al, 2014 ), muscle contraction (Dostanic-Larson et al, 2005 ; Radzyukevich et al, 2009 ), intercellular communications (Matchkov et al, 2007 , 2012 ), and gene expression (Xiao et al, 2002 ; Kulikov et al, 2007 ; Orlov and Hamet, 2015 ; Blanco and Venugopal, 2016 ). Knowledge on the role of Na,K-ATPase and endogenous CTS in intracellular signaling opens new perspectives for modulation of cell function under normal and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Radachlorin has better light penetration of target tissue, as compared to first-generation photosensitizers (18). The anticancer effects of PDT using radachlorin in some in vitro and in vivo cancer models have been reported (19)(20)(21)(22); however, the potential of radachlorin-mediated PDT for the treatment of endometrial adenocarcinoma remains unclear.…”
mentioning
confidence: 99%